Co-location of a Government Child Welfare Unit in a Traditional Aboriginal Agency: A Way Forward in Working in Aboriginal Communities - Kreitzer, Linda; Lafrance, Jean (First Peoples Child & Family Review, 2010)
This article describes the learning that took place in the context of a provincial family enhancement unit within an Aboriginal child welfare agency. Many benefits were identified for the workers, the families, and the relationship to the community. Most notable were the positive effects on non-Aboriginal government staff who were immersed in a more traditional Aboriginal agency. Key learnings include the importance of relationship in child welfare practice, the desire of child welfare workers for greater creativity in their responses to children and families and the need for more supportive leadership in the creation of the conditions necessary for this to happen. Recommendations are made to provincial officials to assist in the creation of such an environment.